Pengaruh Cita Rasa Dan Variasi Produk Terhadap Kepuasan Konsumen Studi Kasus Pada Cafe Kana Eatery Kediri - Ririen Novita Sari; Edy Suwasono; Rike Kusuma Wardhani (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This research discusses the influence of taste and product variety on case study consumer satisfaction at Café Kana Eatery Kediri. This research aims to find out and explain the results of the influence of taste and product variety on case study consumer satisfaction at Café Kana Eatery Kediri. The method used in this research is quantitative descriptive. The population used in this research is Café Kana Eatery Kediri consumers from May to June 2023, totaling 75 people. The sample used in this research was 63 consumers of Café Kana Eatery Kediri who visited from 1 May to 30 June 2023. The sampling method used in this research used purposive sampling. Data processing in this research uses Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression, Determination Coefficient (R2), T Test and F Test. The results of this research are that Taste has a partial effect on Consumer Satisfaction with a significant value of 0.002 < 0.05. Product Variation has a partial effect on Consumer Satisfaction with a significant value of 0.000 < 0.05. Taste and Product Variety simultaneously influence Consumer Satisfaction with a significant value of 0.000 < 0.05.